Forecasting with panel data - Badi H. Baltagi (Deutsche Bundesbank, 2006)
This paper gives a brief survey of forecasting with panel data. Starting with a simple error component regression and surveying best linear unbiased prediction under various assumptions of the disturbance term. This includes various ARMA models as well as spatial autoregressive models. The paper also surveys how these forecasts have been used in panal data applications, running horse races between heterogeneous and homogeneous panel data models using out of sample forecasts.
Keywords: C33; 330; Forecasting; BLUP; Panel Data; Spatial Dependence; Serial Correlation; Prognoseverfahren; Panel; Zeitreihenanalyse; Theorie